Metabonomic profiles delineate potential role of glutamate-glutamine cycle in db/db mice with diabetes-associated cognitive decline. Issue 1 (December 2016) - Zheng, Yongquan; Yang, Yunjun; Dong, Baijun; Zheng, Hong; Lin, Xiaodong; Du, Yao; Li, Xiaokun; Zhao, Liangcai; Gao, Hongchang
Abstract Background Diabetes-associated cognition decline is one of central nervous system complications in diabetic mellitus, while its pathogenic mechanism remains unclear. In this study, 1 H nuclear magnetic resonance-based metabonomics and immunohistochemistry was used to explore key metabolic alterations in hippocampus of type 2 diabeticdb/db mice with cognition decline in order to advance understanding of mechanisms underlying the pathogenesis of the disease. Results Metabonomics reveals that lactate level was significantly increased in hippocampus ofdb/db mice with cognition decline compared with age-matched wild-type mice. Several tricarboxylic acid cycle intermediates including succinate and citrate were reduced in hippocampus ofdb/db mice with cognition decline. Moreover, an increase in glutamine level and a decrease in glutamate and γ-aminobutyric acid levels were observed indb/db mice. Results from immunohistochemistry analysis show that glutamine synthetase was increased and glutaminase and glutamate decarboxylase were decreased indb/db mice. Conclusions Our results suggest that the development of diabetes-associated cognition decline indb/db mice is most likely implicated in a reduction in energy metabolism and a disturbance of glutamate-glutamine shuttling between neurons and astrocytes in hippocampus.